Three Variations on the Theme of Intimacy in Sociology - Maslauskaitė, Aušra (Sociologija. Mintis ir veiksmas, 2000)
The attentiveness towards the human experience in contemporary sociology is evident in the analysis of topics such as intimacy, love, body and others. The article argues that sociological analysis of the phenomena requires sociology to move beyond utilitarianism. This article is grounded on a discussion of the conceptions of intimacy in sociological theories of George Simmel, Peter Berger and Hansfried Kellner, and Anthony Giddens. In the historically-oriented analysis of the conceptual approaches to the phenomena of intimacy, the article suggests that the contemporary theory defines intimacy in a rather individualistic way that does not provide the means to understand the problematique.